Hydroxyapatite coatings: a critical review on electrodeposition parametric variations influencing crystal facet orientation towards enhanced electrochemical sensing. Issue 21 (27th September 2022) - Dev, Priya Ranjan; Anand, Chekkottu Parambil; Michael, David Samuvel; Wilson, P.
Abstract : The possibility of control over crystal facet orientation and microstructure via electrodeposition parametric variation towards enhancement of applicability of nanocomposites. Abstract : Electrochemical deposition presents a promising route toward the fabrication of hydroxyapatite (HAp) coatings attributed to its simplistic approach in the preparation of coatings over complex substrates with control over coating thickness and crystal orientation through variations in electrodeposition parameters. This article aims to consolidate and review the influence of reported parametric determinants associated with electrodeposition thereby providing insight into the outcome of HAp microstructures in terms of Ca/P ratio, crystal growth, and facet orientation of the HAp hexagonal crystal system. Additionally, a discussion on HAp and its composites as viable sensor materials for a myriad of aqueous-based analytes and gaseous molecules is presented. A survey into the application of HAp as a sensor is elaborated, emphasizing the level of sensitivity, selectivity, and sensor response characteristics regarding optimum performance at maximum % sensitivity. Mechanistic insights into the interaction of HAp with analyte species are discussed. Finally, the parameters that include both current density and pH are correlated to determine their synergistic effect as a deciding factor in the growth and preferential orientation of aligned hexagonal HAp crystal domains.